CHEMICAL AND FUNCTIONAL CHARACTERIZATION OF CHILOE’S GIANT GARLIC (Allium ampeloprasum L.) - Peterssen-Fonseca, Darlene; Carrasco-Sandoval, Jonathan; Fernandez-Martinez, Joaquin; Herrero, Miguel; Aqueveque, Pedro; Henriquez-Aedo, Karem; Aranda, Mario (Journal of the Chilean Chemical Society, 2025)
The present work reports the chemical and functional profile of Chiloe’s giant garlic. Applying AOAC’s official methods the proximal content of giant garlic was determined finding a moisture content of 62.34±0.35%, carbohydrates 20.64±0.01%, protein 2.80±0.10%, fat (crude) 0.09±0.00%, ash 0.74±0.02%, and fiber (crude) 13.04±0.01%. Three saccharides [sucrose (5.92±0.02 mg g-1), glucose (0.11±0.00 mg g-1) and fructose (0.46±0.01 mg g-1)], four fatty acids [linoleic acid (57.67±0.00%), palmitic acid (23.46±0.00%), oleic acid (7.20±0.00%), and ⍺-linolenic acid (5.06±0.00%)], and three sulfoxide compounds [alliin (2.66±0.90 mg g-1), methiin (9.61±0.33 mg g-1) and isoalliin (5.02±1.24 mg g-1)] were determined by high-performance thin-layer chromatography (HPTLC), gas chromatography (GC) and HPTLC/mass spectrometry (MS), respectively. Functional profile characterization showed an Oxygen Radical Absorbance Capacity (ORAC) value of 0.250±0.001 mmol TE per 100 g-1 and a total (poly)phenols content (TPC) of 40.66±2.08 mg EAG 100 g-1. (Poly)phenols profile analyzed by liquid chromatography (LC)/MS showed only the presence of caffeic acid (0.57±0.05 μg g-1) and rutin (at traces level). Bioactive molecules with antioxidant (DPPH) and COX-2 inhibition activities were identified through HPTLC (bio)autography and MS analysis, finding the presence of tryptophan (antioxidant) and γ-glutamyl-S-allyl-L-cysteine (GSAC), γ-glutamyl-S-(trans-1-propenyl)-L- cysteine (GSPC), alliin and isoalliin with antioxidant and COX-2 inhibitory activity.